Os sertões de Euclídes da Cunha : uma (re)leitura estético-política da Guerra de Canudos - Oliveira, Ângela Pereira da Silva (2018)
In this research, titled Os sertões de Euclides da Cunha: an aesthetic-political (re) reading of Canudos War, we proceed an analysis of the aesthetic and the political, in order to find new possible readings from Os sertões, by Euclides of Cunha. For this, we identified certain political transformations of Euclides da Cunha, which resulted in his aesthetic change as well. We perceive traces of social and political rupture in Canudos, which can be considered fundamental distinctive qualities of more ethical and solidary ways of life, since they escape the totalizing formulas. We invoke some knowledge in History and Literature, because of their narrative force, use of the affections and the imagination. Tangentially, we take advantage of concepts from some areas, law is one of them. From an interdisciplinary perspective on principle, these concepts, in the context of the Canudos War, help us to reveal a society in the country featured by conservatism and legal positivism. Despite the theological character of the Canudos community, guided by feelings of religiosity, the way of life of urban and wealthy Brazilian society contrasts sharply with the peculiar way of life of the community of the countryside of Belo Monte. In the plots of his antitheses and his paradoxes, Euclides da Cunha, intending to set the republican ideals, reveals a subject, who is a subject of law, whose main aspiration was to live well. The knowledge involved in the writing of Euclides da Cunha, in Os sertões, allows an aesthetic sharing of new worlds and new realities, which collapses certainties, given the crudeness of the facts narrated. For this unveiling, the concepts of autopoiesis, aesthetic regime and interdisciplinarity also contribute. Such concepts allow us to construct this other interpretation that we intend with Os sertões, by Euclides da Cunha.